ETHICS SURROUNDING THE STANFORD PRISON EXPERIMENT - Anjali (International Journal of Multidisciplinary Research and Studies, 2021)
Recent studies (August 14-21, 1971) were carried out at Stanford University in which participants were asked to play the part of either a "prisoner" or a "guard" for a prolonged period of time within the context of a mock prison that had been constructed for the purpose of conducting research. When it became apparent that many of the 'prisoners' were in serious distress and that many of the 'guards' were behaving in ways that brutalised and degraded their fellow subjects, the study had to be prematurely terminated.